Flame retardant gel electrolyte, battery and preparation method thereof

By using brominated alkyl or bromine alkenyl flame retardant polymers and polyethylene glycol diacrylate crosslinking agents in lithium-ion batteries, the problem of insufficient free radical capture at high temperatures has been solved, and the problem of existing electrolytes is improved. The safety and electrochemical properties of the battery are provided.

CN118888838BActive Publication Date: 2024-12-31JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411225550.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2024-12-31
Estimated Expiration
2044-09-03

AI Technical Summary

Technical Problem

The F·free radicals generated by the decomposition of the flame-retardant electrolytes of existing lithium-ion batteries cannot effectively capture the free radicals, resulting in combustion risks and high thermal decomposition temperatures, which limit its development.

Method used

Using flame retardant polymers containing bromine alkyl or bromine alkenyl groups, Br·free radicals are used to form binding to H·free radicals through C-Br bonds, and the chain combustion reaction is terminated, and polyethylene glycol diacrylate is passed. The crosslinking agent forms a crosslinked polymer to enhance lithium ion dissociation and improve ion conductivity.

Benefits of technology

It significantly reduces the combustion risk of electrolytes, improves the safety and electrochemical performance of the battery, and is simple and easy to produce on a large scale.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_10
    Figure SMS_10
  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
Patent Text Reader

Abstract

The present invention relates to the field of battery technology, and in particular to a flame-retardant gel electrolyte, a battery and a method for preparing the same. The flame-retardant gel electrolyte provided comprises a flame-retardant polymer and an electrolyte. In the method for preparing the flame-retardant gel electrolyte, the flame-retardant polymer and the electrolyte are mixed to obtain a flame-retardant gel electrolyte; wherein the raw materials for preparing the flame-retardant polymer include a polymer monomer and a cross-linking agent; the polymer monomer includes bromoacrylate, and the cross-linking agent includes polyethylene glycol diacrylate. The flame-retardant gel electrolyte of the present invention has good flame retardant properties and electrochemical properties, and is beneficial to improving the safety performance and cycle performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a flame retardant gel electrolyte, a battery and a preparation method thereof. Background Art

[0002] At present, the safety of power batteries has received more and more attention. Among them, the safety issues of lithium-ion batteries are mainly caused by thermal runaway caused by mechanical abuse, electrical abuse or thermal abuse of batteries, and the high flammability of electrolytes is the key factor in battery safety problems. Therefore, starting from the intrinsic safety design of electrolytes, the development of flame-retardant electrolytes is of great significance to improving the safety of lithium-ion batteries.

[0003] At present, the solutions to solve the safety problem of lithium batteries mainly include: all-solid-state lithium-ion battery solution, flame retardant addition to electrolyte solution and gel electrolyte solution. Among them, gel electrolyte has a broader development space because the ionic conductivity and chemical properties of gel polymer are closer to liquid electrolytes and the safety performance is closer to solid electrolytes. It can improve the safety of lithium batteries to a certain extent while taking into account excellent ionic conductivity. However, the current gel electrolyte still has certain shortcomings and needs to be further improved. For example, the patent with publication number CN117996176A uses the in-situ copolymerization reaction of perfluorobutyl acrylate monomer and pentaerythritol tetraacrylate crosslinker to develop a flame-retardant perfluorogel polymer electrolyte, which can decompose at high temperature to produce F· free radicals. These free radicals can eliminate the chain combustion reaction of HO· and H· free radicals in the gas phase, thereby reducing the combustion risk of the electrolyte. Although this solution has certain flame retardant properties, the bond energy of the CF bond is large, and the free radicals cannot be effectively captured, and the thermal decomposition temperature is high, which limits its further development.

[0004] In view of this, this application is hereby filed. Summary of the invention

[0005] In view of this, the present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, the present invention provides a flame retardant gel electrolyte, a battery and a preparation method thereof, wherein the flame retardant gel electrolyte has good flame retardant properties and electrochemical properties, and is conducive to improving the safety performance of the battery.

[0006] In order to solve the above technical problems, this application is implemented as follows:

[0007] According to one aspect of the present application, an embodiment of the present application provides a flame retardant gel electrolyte, the flame retardant gel electrolyte comprising a flame retardant polymer and an electrolyte;

[0008] Wherein, the flame retardant polymer has the chemical formula shown in the following formula I:

[0009] Formula I;

[0010] Wherein, the R includes at least one of a brominated alkyl group or a brominated alkenyl group, and the brominated group is a partial substitution or a full substitution; and the value ranges of n, m1, m2, and m3 are 3 to 30, respectively.

[0011] In addition, the flame-retardant gel electrolyte according to the present application may also have the following additional technical features:

[0012] In some embodiments, the electrolyte includes a lithium salt, an organic solvent, and a functional additive.

[0013] In some embodiments, the functional additive includes at least one of vinylene carbonate, fluoroethylene carbonate, 1,3-propane sultone or vinylene sulfate.

[0014] In some embodiments, the lithium salt includes at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium tetrafluoroborate, lithium difluorophosphate, lithium difluorooxalatoborate, and lithium difluorobisoxalatophosphate.

[0015] In some embodiments, the organic solvent includes at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, propyl propionate, ethyl acetate and methyl acetate.

[0016] In some of the embodiments, the concentration of lithium salt in the electrolyte is 0.8 mol / L to 1.5 mol / L.

[0017] In some embodiments, the mass percentage of the functional additive in the electrolyte is 0.5% to 5%.

[0018] According to another aspect of the present application, an embodiment of the present application provides a method for preparing the flame-retardant gel electrolyte, the method comprising:

[0019] Mixing a flame retardant polymer and an electrolyte to obtain a flame retardant gel electrolyte;

[0020] Wherein, the raw materials for preparing the flame retardant polymer include polymer monomers and cross-linking agents;

[0021] The polymer monomer includes bromoacrylate, and the cross-linking agent includes polyethylene glycol diacrylate.

[0022] In some embodiments, the bromoacrylate has a chemical formula as shown in Formula II below:

[0023] Formula II;

[0024] Wherein, the R includes at least one of a brominated alkyl group or a brominated alkenyl group, and the brominated group is a partial substitution or a full substitution.

[0025] In some embodiments, the average molecular weight of the polyethylene glycol diacrylate is 600-1500.

[0026] In some embodiments, the mass ratio of the crosslinking agent to the polymer monomer is (2-4):1.

[0027] In some of the embodiments, the mass ratio of the polymer monomer to the electrolyte is (1% to 3%):1.

[0028] In some embodiments, the raw materials for preparing the flame retardant polymer further include an initiator.

[0029] In some embodiments, the method for preparing the flame retardant gel electrolyte comprises the following steps:

[0030] Mixing polymer monomers, a cross-linking agent, an initiator and an electrolyte to obtain a precursor solution;

[0031] The precursor solution is polymerized under heating and pressure conditions to form a cross-linked flame retardant polymer.

[0032] In some embodiments, the polymerization reaction conditions include: reaction temperature of 60° C. to 90° C., reaction pressure of 0.2 MPa to 1.5 MPa, and reaction time of 12 h to 48 h.

[0033] In some embodiments, the mass ratio of the initiator to the polymer monomer is (0.1-0.5):1.

[0034] In some embodiments, the initiator includes at least one of azobisisobutyronitrile, sodium persulfate, or tert-butyl peroxide.

[0035] According to another aspect of the present application, an embodiment of the present application provides a battery, the battery comprising:

[0036] A dry cell, the dry cell comprising a positive electrode and a negative electrode; and

[0037] The flame retardant gel electrolyte as described above or the flame retardant gel electrolyte prepared according to the method described above.

[0038] According to another aspect of the present application, an embodiment of the present application provides a method for preparing a battery, the method comprising:

[0039] Mixing polymer monomers, a cross-linking agent, an initiator and an electrolyte to obtain a precursor solution;

[0040] The precursor solution is injected into a dry battery cell, and after standing at room temperature, forming and aging, an in-situ hot pressing polymerization reaction is performed to obtain a battery having the aforementioned flame retardant gel electrolyte.

[0041] In some embodiments, the conditions of the in-situ hot pressing polymerization reaction include: a reaction temperature of 60° C. to 90° C., a reaction pressure of 0.2 MPa to 1.5 MPa, and a reaction time of 12 h to 48 h.

[0042] In some embodiments, the temperature of the room temperature standing is 22° C. to 28° C., and the time of the room temperature standing is 24 h to 48 h.

[0043] In some embodiments, the formation current is 0.01C to 0.1C, the formation temperature is 22°C to 28°C, and the formation time is 2h to 10h.

[0044] In some embodiments, the aging temperature is 35° C. to 45° C., and the aging time is 12 h to 48 h.

[0045] In some of the embodiments, after the in-situ hot-pressing polymerization reaction, the steps of secondary formation, exhaust and volume separation are also included; wherein the current of the secondary formation is 0.1C to 0.5C, and the charging cut-off voltage is 4.2V to 4.35V.

[0046] In some embodiments, the exhaust time is 5s to 30s, and the exhaust vacuum bag is -98kPa to -50kPa.

[0047] Implementing the technical solution of the present invention has at least the following beneficial effects:

[0048] In the embodiment of the present application, the flame-retardant gel electrolyte provided includes a flame-retardant polymer and an electrolyte, wherein the chemical formula of the flame-retardant polymer contains bromine (Br)-containing groups such as bromoalkyl and bromoalkenyl; thus, the C-Br bond of the flame-retardant gel electrolyte will break at high temperatures, and the Br· free radicals generated by decomposition tend to combine with H· free radicals, which is beneficial to terminate the chain combustion reaction, thereby reducing the combustion risk of the electrolyte, and further improving the safety performance of the battery. In addition, the oxygen-containing groups in the flame-retardant polymer can coordinate with lithium ions, promote the dissociation of lithium salts, enhance ion conductivity, and help improve the electrochemical performance of the electrolyte.

[0049] Additional aspects and advantages of the present application will be given in part in the following description, and in part will become obvious from the following description, or will be learned through practice of the present invention. DETAILED DESCRIPTION

[0050] The present application is further described below in conjunction with specific embodiments. It should be understood that these embodiments of the present application are only used to illustrate the present application and are not used to limit the scope of the present application.

[0051] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range or the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0052] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0053] If there is no special explanation, the "include" and "comprising" mentioned in this application represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0054] Generally, when the temperature of the battery increases, the non-aqueous organic solvent used to prepare the gel electrolyte is decomposed, thereby generating highly active free radicals (such as HO· free radicals and H· free radicals) and burning at the same time; in this case, because the free radical generation reaction is an exothermic reaction, the combustion reaction of the organic solvent may be a chain reaction, thereby causing the battery to burn or catch fire. Therefore, starting from the intrinsic safety design of the electrolyte, the development of flame-retardant electrolytes is of great significance to improving the safety of batteries such as lithium batteries.

[0055] However, the flame-retardant electrolytes in the related art still have certain shortcomings. For example, by decomposing at high temperature to produce F· free radicals, the free radicals can be used to eliminate the HO· and H· free radical chain combustion reactions in the gas phase, thereby reducing the combustion risk of the electrolyte. Although it has certain flame retardant properties, the bond energy of the CF bond is large, it cannot effectively capture free radicals, and the thermal decomposition temperature is high. In view of the deficiencies in the prior art, the inventors of the present application have proposed the technical solution of the present invention after a lot of research and practice. The technical solution, its implementation process and principle will be further explained as follows.

[0056] In some embodiments, the present application provides a flame retardant gel electrolyte, the flame retardant gel electrolyte comprising a flame retardant polymer and an electrolyte;

[0057] Wherein, the flame retardant polymer has the chemical formula shown in the following formula I:

[0058] Formula I;

[0059] Wherein, R includes at least one of a brominated alkyl group or a brominated alkenyl group, and the brominated group is a partial substitution or a full substitution; and the value ranges of n, m1, m2, and m3 are 3 to 30, respectively.

[0060] It is understood that bromoalkyl refers to an alkyl group in which at least one H atom is replaced by a bromine (Br) atom; and bromoalkenyl refers to an alkenyl group in which at least one H atom is replaced by a bromine (Br) atom.

[0061] In the above-mentioned bromoalkyl, bromo is partially substituted or fully substituted, which means that a part of the H atoms in the alkyl group is replaced by Br atoms, or all the H atoms in the alkyl group are replaced by Br atoms, that is, the bromoalkyl group may contain one or more Br atoms. Similarly, in the bromoalkenyl group, bromo is partially substituted or fully substituted, which means that a part of the H atoms in the alkenyl group is replaced by Br atoms, or all the H atoms in the alkenyl group are replaced by Br atoms, that is, the bromoalkenyl group may contain one or more Br atoms.

[0062] Optionally, the bromoalkyl group may be a bromoalkyl group having 1 to 5 carbon atoms, i.e., a bromoC1 to C5 alkyl group. As an example, the bromoalkyl group may be bromomethyl, bromoethyl, bromopropyl, bromobutyl, bromopentane, etc. Of course, according to actual conditions, in other embodiments, the bromoalkyl group may also be a bromoalkyl group having more than 5 carbon atoms.

[0063] Optionally, the bromoalkenyl group may be a bromoalkenyl group having 2 to 7 carbon atoms, i.e., a brominated C2 to C7 alkenyl group. As an example, the bromoalkenyl group may be bromoethylene, bromopropylene, bromobutylene, etc. Of course, according to actual conditions, in other embodiments, the bromoalkyl group may also be a bromoalkenyl group having more than 7 carbon atoms.

[0064] In the above formula I, the value range of n is 3 to 30 (n is an integer), for example, n can be 3, 4, 5, 6, 8, 10, 12, 15, 18, 20, 22, 25, 28, 30 or a range consisting of any two of the above values.

[0065] In the above formula I, the value range of m1 is 3 to 30 (m1 is an integer). For example, m1 can be 3, 4, 5, 6, 8, 10, 12, 15, 18, 20, 22, 25, 28, 30 or a range consisting of any two of the above values.

[0066] In the above formula I, the value range of m2 is 3 to 30 (m2 is an integer). For example, m2 can be 3, 4, 5, 6, 8, 10, 12, 15, 18, 20, 22, 25, 28, 30 or a range consisting of any two of the above values.

[0067] In the above formula I, the value range of m3 is 3 to 30 (m3 is an integer). For example, m3 can be 3, 4, 5, 6, 8, 10, 12, 15, 18, 20, 22, 25, 28, 30 or a range consisting of any two of the above values.

[0068] In the present application, the flame retardant polymer in the flame retardant gel electrolyte may be a cross-linked product of a polymer monomer and a cross-linking agent, wherein the polymer monomer includes bromoacrylate, and the cross-linking agent includes polyethylene glycol diacrylate (PEGDA).

[0069] Therefore, the flame retardant gel electrolyte provided can improve the flame retardant performance of the electrolyte, and after being applied to batteries such as lithium batteries, it can improve the safety performance of lithium batteries. Specifically:

[0070] The inventors of the present application have discovered that the combination of bromoacrylate and polyethylene glycol diacrylate (PEGDA) can achieve synergy and effectively solve the problems of flame retardancy and electrochemical performance, significantly improve the flame retardancy and electrochemical properties of the electrolyte, and improve the safety and ionic conductivity of the battery.

[0071] On the one hand, the flame-retardant polymer in the flame-retardant gel electrolyte contains bromoalkyl or bromoalkenyl groups, so that the C-Br bond of the formed gel electrolyte will break at high temperature, and the Br· free radicals produced by decomposition tend to combine with H· free radicals, which is conducive to terminating the chain combustion reaction, thereby reducing the combustion risk of the electrolyte and improving the safety of the battery. On the other hand, the flame-retardant polymer contains a large number of polyethylene glycol (PEO) structural units, which can be used to dissolve a large amount of lithium salts and has high ionic conductivity. In other words, the oxygen-containing groups in the polymer structure can coordinate with lithium ions, promote the dissociation of lithium salts, and enhance ionic conductivity.

[0072] Therefore, the present invention imparts excellent ionic conductivity and flame retardancy to the flame retardant gel electrolyte through the synergy of a flame retardant polymer with a specific structure and an electrolyte (such as a lithium salt electrolyte solution), thereby improving the electrochemical properties and safety performance of the electrolyte. In addition, the preparation method is simple and easy to mass produce.

[0073] At the same time, compared with the F· free radicals generated by decomposition at high temperature in the prior art, the bond energy of the C-Br bond in the bromoacrylate component used in the present invention is weaker than the CF bond, and the flame retardant effect of the bromine-containing flame retardant polymer is better than that of the fluorine-containing flame retardant polymer agent, which can effectively alleviate the defects of the existing CF bond having a large bond energy, being unable to effectively capture free radicals, and having a high thermal decomposition temperature. In addition, the double bond structure in the cross-linking agent polyethylene glycol diacrylate provides a good cross-linking reaction site, which can form a cross-linked network polymer. At the same time, the -CH2CH2O- segment in its molecular structure can provide more electron-donating sites, which can have a strong solvation effect with lithium salts and promote the dissociation of lithium ions. Based on this, batteries assembled with flame-retardant gel electrolytes, such as soft-pack lithium-ion batteries, not only have good electrochemical properties, but also have significantly improved safety. Thermal runaway is triggered by a heating rod at 100% SOC. During the whole process, the soft-pack battery does not catch fire or explode, but only smokes, and there is no leakage of electrolyte.

[0074] In addition, in some preferred embodiments, when preparing a battery, the flame-retardant gel electrolyte can be polymerized in situ inside the battery, ensuring the contact between the electrolyte and the electrode material and reducing the internal resistance of the battery; and the electrolyte precursor improves the chemical stability of the gel electrolyte through cross-linking between molecular chains generated by the monomer polymer, which can enhance the stability of the battery electrolyte. At the same time, the gel electrolyte can limit the fluidity of the flame retardant (flame retardant polymer), reduce the side reactions between the flame retardant and the electrode material, and help to jointly improve the cycle capacity and capacity of the battery.

[0075] In the present application, the electrolyte in the flame-retardant gel electrolyte may adopt the components of conventional liquid electrolytes in the industry.

[0076] In some embodiments, the electrolyte includes a lithium salt, an organic solvent, and a functional additive.

[0077] In some embodiments, the lithium salt includes, but is not limited to, any one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium tetrafluoroborate, lithium difluorophosphate, lithium difluorooxalatoborate and lithium difluorobis(oxalato)phosphate, or a combination of at least two thereof. For the sake of brevity, the combinations within the above range are not listed one by one.

[0078] In addition, in other embodiments, the lithium salt in the above electrolyte is not limited to the types listed above. Under the condition of meeting the basic requirements of lithium salt in conventional battery electrolyte, the lithium salt can also be of other types, which will not be described in detail one by one here.

[0079] In some embodiments, the concentration of the lithium salt in the electrolyte is 0.8 mol / L to 1.5 mol / L (M). As an example, the concentration of the lithium salt can be 0.8 mol / L, 0.9 mol / L, 1.0 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L, 1.5 mol / L, etc.

[0080] In some embodiments, the organic solvent in the electrolyte may be an ester solvent, such as a chain carboxylic acid ester compound and / or a cyclic carbonate compound, etc. As an example, the organic solvent includes, but is not limited to, any one or a combination of at least two of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, propyl propionate, ethyl acetate and methyl acetate. For the sake of brevity, the combinations within the above range are not listed one by one.

[0081] In addition, in other embodiments, the organic solvent in the electrolyte is not limited to the types listed above, and other types may be used. The organic solvent may be a conventional organic solvent type in the electrolyte of the battery, which will not be described in detail one by one here.

[0082] In some embodiments, the functional additive includes, but is not limited to, any one or a combination of at least two of vinylene carbonate, fluoroethylene carbonate, 1,3-propane sultone or vinylene sulfate. For the sake of brevity, the combinations within the above range are not listed one by one.

[0083] In some embodiments, the mass percentage of the functional additive in the electrolyte is 0.5% to 5%. As an example, the mass percentage of the functional additive in the electrolyte is 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, or a range consisting of any two of the above values.

[0084] In some embodiments, the present application also provides a method for preparing a flame retardant gel electrolyte, the method comprising:

[0085] Mixing a flame retardant polymer and an electrolyte to obtain a flame retardant gel electrolyte;

[0086] The raw materials for preparing the flame retardant polymer include polymer monomers and cross-linking agents; the polymer monomers include brominated acrylate, and the cross-linking agent includes polyethylene glycol diacrylate.

[0087] In the present application, the flame retardant polymer may be a cross-linked product of a polymer monomer and a cross-linking agent, that is, the flame retardant polymer may be obtained by cross-linking polymerization of a polymer monomer bromoacrylate and a cross-linking agent polyethylene glycol diacrylate (PEGDA) under the action of an initiator.

[0088] In some embodiments, the method for preparing the flame retardant gel electrolyte comprises the following steps:

[0089] Mixing polymer monomers, a cross-linking agent, an initiator and an electrolyte to obtain a precursor solution;

[0090] The precursor solution is polymerized under heating and pressure conditions to form a cross-linked flame retardant polymer.

[0091] Thus, in a preferred embodiment of the present application, a flame-retardant gel electrolyte can be prepared by in-situ thermal polymerization process, using bromoacrylate as a polymer monomer and polyethylene glycol diacrylate as a cross-linking agent, so that the bromoacrylate and polyethylene glycol diacrylate are copolymerized in situ. The present invention uses bromoacrylate as a polymer monomer and polyethylene glycol diacrylate as a cross-linking agent to prepare a flame-retardant polymer. The bond energy of the C-Br bond in the bromoacrylate component is weaker than that of the CF bond. The flame retardant effect of the bromine-containing flame-retardant polymer is better than that of the fluorine-containing flame-retardant polymer agent, which can effectively alleviate the defects of the existing CF bond having a large bond energy, being unable to effectively capture free radicals, and having a high thermal decomposition temperature. In addition, the double bond structure in the cross-linking agent polyethylene glycol diacrylate provides a good cross-linking reaction site, which can form a cross-linked network polymer. At the same time, the -CH2CH2O- segment in its molecular structure can provide more electron-donating sites, which can have a strong solvation effect with lithium salts and promote the dissociation of lithium ions. Thus, the Br· free radicals produced by decomposition combine with the H· free radicals, which is beneficial to terminate the chain combustion reaction, thereby reducing the combustion risk of the electrolyte and improving the safety performance of the battery; and the oxygen-containing groups in the polymer structure can coordinate with lithium ions, promote the dissociation of lithium salts, enhance ion conductivity, and thus improve the electrochemical performance of the battery.

[0092] The present invention utilizes a cross-linking agent to link polymer molecules to each other to generate a three-dimensional network structure, which has higher chemical and thermal stability, is beneficial to improving the stability of the gel electrolyte, and makes the battery performance stable and long-lasting.

[0093] In some embodiments, the polymer monomer, bromoacrylate, has the chemical formula shown in Formula II below:

[0094] Formula II;

[0095] Wherein, R includes at least one of a brominated alkyl group or a brominated alkenyl group, and the brominated group is a partial substitution or a full substitution.

[0096] It will be appreciated that the R groups in formula II may be compatible with the R groups in formula I.

[0097] The study found that further controlling the structure of the bromoacrylate monomer can help further improve the electrochemical interaction between the components, further improve the stability of the structure, and further improve the flame retardancy and electrochemical properties of the flame-retardant gel electrolyte.

[0098] In some specific embodiments, the bromoacrylate may be 3-bromo-2,2-bis(bromomethyl)propyl acetate (CAS: 3580-97-0).

[0099] Optionally, the chemical formula of the bromoacrylate is as shown in Formula II-1 (CAS: 3217-37-6):

[0100] Formula II-1.

[0101] In some specific embodiments, the chemical formula of bromoacrylate is shown in the following formula II-2 (CAS: 3102-74-7):

[0102] Formula II-2.

[0103] In some specific embodiments, the chemical formula of bromoacrylate is shown in the following formula II-3 (CAS: 64046-90-8):

[0104] Formula II-3.

[0105] Of course, bromoacrylate also has chemical formulas of other structural forms, which are not listed here one by one.

[0106] Optionally, when the bromoacrylate is a substance of the chemical formula shown in the above formula II-1, the flame retardant polymer has the chemical formula shown in the following formula I-1:

[0107] Formula Ⅰ-1.

[0108] In some embodiments, the crosslinking agent, polyethylene glycol diacrylate, has an average molecular weight of 600 to 1500. As an example, the average molecular weight of polyethylene glycol diacrylate can be 600, 700, 800, 900, 1000, 1100, 1200, 1300, 1400, 1500, etc.

[0109] As an example, the chemical formula of polyethylene glycol diacrylate (CAS: 26570-48-9) is shown in the following formula III:

[0110] Formula III;

[0111] The value range of n is 3 to 30.

[0112] The present invention utilizes polyethylene glycol diacrylate as a crosslinking agent, wherein the double bond structure provides a good crosslinking reaction site, and can form a crosslinked network polymer. Meanwhile, the -CH2CH2O- segment in its molecular structure can provide more electron-donating sites, and can have a strong solvation effect with lithium salts, promoting the dissociation of lithium ions; that is, the oxygen-containing groups therein can coordinate with lithium ions, promote the dissociation of lithium salts, and enhance ion conductivity.

[0113] The polyethylene glycol diacrylate crosslinking agent can link polymer molecules to each other to form a three-dimensional network structure with higher chemical and thermal stability, which is beneficial to improving the stability of the gel electrolyte and making the battery performance stable and long-lasting.

[0114] In some embodiments, the mass ratio of the crosslinking agent to the polymer monomer is (2-4): 1. As an example, the mass ratio of the crosslinking agent to the polymer monomer can be 2:1, 3:1, 4:1, etc.

[0115] By controlling the mass ratio of the cross-linking agent to the polymer monomer within the above range, the cross-linking agent is used to fully cross-link the bromoacrylate monomer without affecting the electrochemical performance of the battery. If the amount of the cross-linking agent added is too low, the cross-linking reaction of the bromoacrylate monomer may not be sufficient. If the amount of the cross-linking agent added is too high, it may affect other electrochemical properties of the battery, such as the internal resistance and capacity.

[0116] In some embodiments, the mass ratio of the polymer monomer to the electrolyte is (1% to 3%): 1. As an example, the mass ratio of the polymer monomer to the electrolyte may be 1%: 1, 1.5%: 1, 2%: 1, 2.5%: 1, 3%: 1, etc.

[0117] By controlling the mass ratio of polymer monomers to electrolyte within the above range, the prepared flame-retardant gel electrolyte can play a role in flame retardancy and improve the electrochemical performance of the battery. If the mass percentage of the polymer monomer is too low, the effect on the electrolyte is not obvious, and the improvement of the flame retardant effect is not obvious; if the mass percentage of the polymer monomer is too high, it may affect the content of ions in the electrolyte and reduce the specific capacity of the battery.

[0118] In some embodiments, the raw materials for preparing the flame retardant polymer further include an initiator. The addition of the initiator can accelerate the reaction rate of the cross-linking reaction of the bromoacrylate monomer.

[0119] Optionally, the mass ratio of the initiator to the polymer monomer is (0.1-0.5): 1. As an example, the mass ratio of the initiator to the polymer monomer may be 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, etc.

[0120] In the present application, the initiator may be a conventional component in the industry, and the initiator is an initiator capable of initiating polymerization of bromoacrylate monomers.

[0121] In some embodiments, the initiator includes, but is not limited to, at least one of azobisisobutyronitrile, sodium persulfate, or tert-butyl peroxide.

[0122] Preferably, the initiator is azobisisobutyronitrile.

[0123] In some embodiments, the conditions of the polymerization reaction include: a reaction temperature of 60° C. to 90° C., a reaction pressure of 0.2 MPa to 1.5 MPa, and a reaction time of 12 h to 48 h.

[0124] In some embodiments, the present application provides a battery, the battery comprising:

[0125] A dry cell, comprising a positive electrode and a negative electrode; and

[0126] The flame retardant gel electrolyte as above or the flame retardant gel electrolyte prepared according to the above method.

[0127] In the present application, the battery may be a lithium-ion battery, or may be a sodium-ion battery, a magnesium-ion battery or other types of batteries.

[0128] The battery structure of the present application includes but is not limited to soft-pack lithium-ion batteries, square hard-shell batteries or cylindrical hard-shell batteries, etc.

[0129] In this embodiment, the positive electrode and negative electrode in the battery respectively include a current collector and an active material layer arranged on the surface of the current collector. The present application does not limit the specific materials and structures of the current collector and the active material layer in the positive electrode and the negative electrode, and the positive electrode and negative electrode structures and components that are well known in the art and can be used for secondary batteries can be selected.

[0130] As an example, the positive electrode active material in the active material layer in the positive electrode can be a ternary material, such as a ternary high nickel positive electrode LiNi x Co y Mn 1-x-y O2 (0.8≤x<1); Of course, the type of the positive electrode active material is not limited thereto.

[0131] As an example, the negative electrode active material in the active material layer in the negative electrode may be a carbon-based material and / or a silicon-based material, such as graphite, or a mixture of graphite and silicon-based materials; of course, the type of negative electrode active material is not limited thereto.

[0132] Since the battery provided in the embodiment of the present invention adopts all the technical solutions of the above embodiments, it has at least all the beneficial effects brought by the technical solutions of the above embodiments, which will not be described one by one here.

[0133] In some embodiments, the present application provides a method for preparing a battery, the method comprising:

[0134] Mixing polymer monomers, a cross-linking agent, an initiator and an electrolyte to obtain a precursor solution;

[0135] The precursor solution is injected into the dry battery cell, and after standing at room temperature, forming and aging, an in-situ hot pressing polymerization reaction is carried out to obtain a battery having the aforementioned flame retardant gel electrolyte.

[0136] In the present application, during the preparation of the battery, a flame-retardant gel electrolyte can be prepared by an in-situ thermal polymerization process. Thus, after the liquid injection and formation, the unsaturated double bonds are directly polymerized by heating to obtain an integrated flame-retardant gel electrolyte inside the battery, which can provide good interface contact between the electrode and the electrolyte.

[0137] The present invention has been found that the synergistic components of the present invention, in combination with the in-situ cross-linking method, can further cooperate to successfully construct a flame-retardant gel electrolyte with a complete structure and flame-retardant effect in the battery, thereby effectively improving the electrochemical performance and safety of the resulting battery.

[0138] The method of the present invention can prepare a flame-retardant gel electrolyte without substantially changing the existing process of the lithium battery, and has the advantages of simple operation and easy implementation.

[0139] In some specific embodiments, the method for preparing a battery mainly includes the following steps:

[0140] S10, preparing a precursor solution.

[0141] In step S10, polymer monomers, crosslinking agents, initiators and electrolytes are mixed to obtain a precursor solution. Specifically:

[0142] At room temperature, polymer monomers, crosslinking agents and initiators are added to a conventional liquid electrolyte and mixed evenly to obtain a precursor solution. Among them, the polymer monomer can be selected from bromoacrylate, the crosslinking agent can be selected from polyethylene glycol diacrylate, and the initiator can be selected from azobisisobutyronitrile, etc. The electrolyte includes a lithium salt, an organic solvent and a functional additive. Among them, the lithium salt includes, but is not limited to, any one or a combination of at least two of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bistrifluoromethylsulfonamide, lithium tetrafluoroborate, lithium difluorophosphate, lithium difluorooxalate borate and lithium difluorobisoxalate phosphate. In the electrolyte, the concentration of lithium salt is 0.8 mol / L to 1.5 mol / L (M). The organic solvent in the electrolyte can be an ester solvent. As an example, the organic solvent includes, but is not limited to, any one or a combination of at least two of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, propyl propionate, ethyl acetate and methyl acetate. The functional additive includes, but is not limited to, any one of vinylene carbonate, fluoroethylene carbonate, 1,3-propane sultone or vinylene sulfate or a combination of at least two thereof. The mass percentage of the functional additive in the electrolyte is 0.5% to 5%.

[0143] In some embodiments, the mass ratio of the crosslinking agent to the polymer monomer is (2-4): 1. The mass ratio of the initiator to the polymer monomer is (0.1-0.5): 1. The mass ratio of the polymer monomer to the electrolyte is (1%-3%): 1.

[0144] S20, performing the processes of standing, forming (primary forming) and aging.

[0145] In step S20, the precursor solution prepared in step S10 is injected into the dry battery cell, and after injection, the cell is left to stand at room temperature, followed by formation, exhaust and aging.

[0146] Optionally, the dry cell comprises a positive electrode and a negative electrode, wherein the positive electrode active material in the active material layer in the positive electrode can be a ternary material, such as a ternary high nickel positive electrode LiNi x Co y Mn 1-x-y O2 (0.8≤x<1). The negative electrode active material in the active material layer in the negative electrode may be a carbon-based material and / or a silicon-based material, such as graphite, or a mixture of graphite and silicon-based materials.

[0147] In some embodiments, in step S20, the temperature of the room temperature standing is 22°C to 28°C (25±3°C), and the time of the room temperature standing is 24h to 48h. The room temperature standing can make the reaction solution fully infiltrated.

[0148] As an example, the temperature for standing at room temperature can be 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C, etc., and the time for standing at room temperature can be 24h, 28h, 30h, 32h, 36h, 28h, 40h, 48h, etc.

[0149] In some embodiments, in step S20, the forming current is 0.01C to 0.1C, the forming temperature is 22°C to 28°C, and the forming time is 2h to 10h.

[0150] As an example, the formation current can be 0.01C, 0.02C, 0.03C, 0.04C, 0.05C, 0.06C, 0.08C, 0.1C, etc., the formation temperature can be 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C, etc.; the formation time can be 2h, 3h, 4h, 5h, 6h, 8h, 10h, etc.

[0151] In some embodiments, in step S20, the exhaust time is 5 to 30 seconds, and the exhaust vacuum degree is -98 kPa to -50 kPa.

[0152] As an example, the exhaust time can be 5s, 10s, 15s, 20s, 25s, 30s, etc., and the exhaust vacuum degree can be -98kPa, -90kPa, -80kPa, -70kPa, -60kPa, -50kPa, etc.

[0153] In some embodiments, in step S20, the aging temperature is 35° C. to 45° C., and the aging time is 12 h to 48 h.

[0154] As an example, the aging temperature can be 35°C, 36°C, 38°C, 40°C, 42°C, 45°C, etc.; the aging time can be 12h, 18h, 20h, 24h, 30h, 36h, 48h, etc.

[0155] S30, performing in-situ hot pressing polymerization reaction.

[0156] In step S30, the battery cell obtained in step S20 is placed in a high temperature environment for in-situ hot pressing polymerization to form a cross-linked polymer network, thereby obtaining a lithium ion battery cell with a flame retardant gel electrolyte.

[0157] In some embodiments, in step S30, the conditions of the in-situ hot pressing polymerization reaction include: a reaction temperature of 60° C. to 90° C., a reaction pressure of 0.2 MPa to 1.5 MPa, and a reaction time of 12 h to 48 h.

[0158] As an example, the reaction temperature can be 60°C, 65°C, 70°C, 75°C, 80°C, 90°C, etc.; the reaction pressure can be 0.2MPa, 0.3MPa, 0.5MPa, 0.8MPa, 1MPa, 1.2MPa, 1.5MPa, etc.; the reaction time can be 12h, 18h, 20h, 24h, 30h, 36h, 48h, etc.

[0159] Step S40, performing secondary formation, exhaust and volume separation processes.

[0160] In step S40, the battery cell obtained in step S20 is subjected to secondary formation, exhaust, and capacity separation to obtain a semi-solid lithium-ion battery.

[0161] In some embodiments, in step S40, the secondary charge current is 0.1C to 0.5C, and the charge cut-off voltage is 4.2V to 4.35V.

[0162] As an example, the secondary current can be 0.1C, 0.2C, 0.3C, 0.4C, 0.5C, etc., and the charging cut-off voltage can be 4.2V, 4.25V, 4.3V, 4.35V, etc.

[0163] In some embodiments, in step S40, the exhaust time is 5s to 30s, and the exhaust vacuum bag is -98kPa to -50kPa.

[0164] As an example, the exhaust time can be 5s, 10s, 15s, 20s, 25s, 30s, etc., and the exhaust vacuum degree can be -98kPa, -90kPa, -80kPa, -70kPa, -60kPa, -50kPa, etc.

[0165] In summary, the flame retardant gel electrolyte provided can improve the flame retardant properties of the electrolyte. When applied to batteries such as lithium batteries, it can improve the safety performance of the lithium batteries and also improve the electrochemical properties of the lithium batteries such as cycle performance.

[0166] In order to better understand the present invention, the specific implementation process of the present invention will be described in detail below in a specific implementation mode. The implementation methods described below are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application. If no specific technology or conditions are specified in the implementation method, the technology or conditions described in the literature in the field or the product specification shall be followed.

[0167] Example 1

[0168] 1. Preparation of electrolyte

[0169] Ethyl methyl carbonate (EMC), diethyl carbonate (DEC) and ethylene carbonate (EC) are mixed in a volume ratio of 5:2:3, lithium hexafluorophosphate (LiPF6) is added to make the lithium salt concentration reach 1.2 mol / L, and then 7 wt% of fluoroethylene carbonate (FEC), 0.5 wt% of 1,3-propene sultone (PST), and 1 wt% of lithium difluorooxalatoborate (LiDFOB) are added relative to the total mass of the electrolyte and stirred and mixed evenly to obtain an electrolyte.

[0170] 2. Preparation of dry cells

[0171] The positive electrode active material is the ternary positive electrode material LiNi x Co y Mn 1-x-y O2 (0.9≤x<1,0<y≤0.1), conductive carbon black (Super-P Li), binder multi-walled carbon nanotubes (MWCNT), and binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 97.5%:1%:0.25%:1.25% to obtain a mixed material, and the mixed material is fully stirred in N-methylpyrrolidone (NMP) to obtain a positive electrode slurry for the corresponding positive electrode sheet.

[0172] The negative electrode active material artificial graphite, silicon oxide negative electrode, conductive agent conductive carbon black (Super-P Li), dispersant sodium carboxymethyl cellulose (CMC), binder polyacrylic acid (PAA), binder styrene butadiene rubber (SBR) are mixed in a mass ratio of 88.5%: 7.25%: 1%: 0.05%: 0.5%: 1.2%: 1.5% to obtain a mixed material, and the mixed material is fully stirred in deionized water to obtain the negative electrode slurry of the corresponding negative electrode sheet.

[0173] After stirring and slurrying, the positive electrode slurry and the negative electrode slurry are coated on 12μm thick aluminum foil and 6μm thick copper foil respectively. After drying, they are rolled, cut, slit, wound and other processes to make 20Ah soft-pack batteries.

[0174] 3. Preparation of batteries

[0175] S10. Take 50g of the basic electrolyte (the electrolyte prepared in step 1 above) at room temperature, add 0.5g of bromoacrylate (the chemical formula of the bromoacrylate is shown in formula II-1 above, CAS: 3217-37-6), 1g of cross-linking agent polyethylene glycol diacrylate and 0.1g of initiator azobisisobutyronitrile, stir evenly to obtain a colorless and transparent precursor solution.

[0176] S20, after thorough drying, the dry cell is injected with the precursor solution, and then left at room temperature for 24 hours, followed by formation, exhaust and aging. The formation is carried out at a current of 0.05C for 5 hours, followed by exhaust at a vacuum degree of -98kPa for 5 seconds, and the aging temperature is 40°C for 36 hours.

[0177] S30, placing the battery cell obtained in step S20 in a high temperature environment of 70°C for in-situ hot pressing polymerization, with a polymerization reaction time of 24 hours and a pressure of 0.2 MPa, to solidify the electrolyte gel to form a flame-retardant gel electrolyte.

[0178] S4: The battery cell obtained in S30 is subjected to secondary charge formation at a current of 0.2C, with a charge cut-off voltage of 4.2V; then, the battery cell is vented with a vacuum degree of -98kPa and a venting time of 5s; and then, a semi-solid lithium-ion battery is obtained after conventional capacity division.

[0179] Example 2

[0180] Embodiment 2 is basically the same as Embodiment 1, and the main difference is:

[0181] In the preparation of the battery, in step S10, 50 g of the basic electrolyte (the electrolyte prepared in step 1 above) is taken at room temperature, 1.5 g of bromoacrylate (the chemical formula of the bromoacrylate is shown in formula II-1 above, CAS: 3217-37-6), 3 g of cross-linking agent polyethylene glycol diacrylate and 0.6 g of initiator azobisisobutyronitrile are added, and stirred evenly to obtain a colorless and transparent precursor solution.

[0182] The rest are the same as in Example 1.

[0183] Example 3

[0184] Embodiment 3 is basically the same as Embodiment 1, and the main difference is:

[0185] In the preparation of the battery, in step S10, 50 g of the basic electrolyte (the electrolyte prepared in step 1 above) is taken at room temperature, 1.0 g of bromoacrylate (the chemical formula of the bromoacrylate is shown in formula II-1 above, CAS: 3217-37-6), 4.0 g of cross-linking agent polyethylene glycol diacrylate and 0.5 g of initiator azobisisobutyronitrile are added, and stirred evenly to obtain a colorless and transparent precursor solution.

[0186] The rest are the same as in Example 1.

[0187] Example 4

[0188] Embodiment 4 is basically the same as Embodiment 1, and the main difference is:

[0189] In the preparation of the battery, in step S10, the chemical formula of the bromoacrylate is as shown in the above formula II-2, CAS: 3102-74-7.

[0190] The rest are the same as in Example 1.

[0191] Example 5

[0192] Embodiment 5 is basically the same as Embodiment 1, and the main difference is:

[0193] In the preparation of the battery, in step S10, the chemical formula of the bromoacrylate is as shown in the above formula II-3, CAS: 64046-90-8.

[0194] The rest are the same as in Example 1.

[0195] Example 6

[0196] Embodiment 6 is basically the same as Embodiment 1, and the main difference is:

[0197] In the preparation of the battery, in step S30, the battery cell obtained in step S20 is placed in a high temperature environment of 60°C for in-situ hot pressing polymerization, the polymerization reaction time is 48 hours, the pressure is 1.5 MPa, and the electrolyte gel is solidified to form a flame retardant gel electrolyte.

[0198] The rest are the same as in Example 1.

[0199] Example 7

[0200] Embodiment 7 is basically the same as Embodiment 1, and the main difference is:

[0201] In the preparation of the battery, in step S30, the battery cell obtained in step S20 is placed in a high temperature environment of 90°C for in-situ hot pressing polymerization, the polymerization reaction time is 12 hours, the pressure is 1.0 MPa, and the electrolyte gel is solidified to form a flame retardant gel electrolyte.

[0202] The rest are the same as in Example 1.

[0203] Comparative Example 1

[0204] 1. Preparation of electrolyte

[0205] Ethyl methyl carbonate (EMC), diethyl carbonate (DEC) and ethylene carbonate (EC) are mixed in a volume ratio of 5:2:3, lithium hexafluorophosphate (LiPF6) is added to make the lithium salt concentration reach 1.2 mol / L, and then 7 wt% of fluoroethylene carbonate (FEC), 0.5 wt% of 1,3-propene sultone (PST), and 1 wt% of lithium difluorooxalatoborate (LiDFOB) are added relative to the total mass of the electrolyte and stirred and mixed evenly to obtain an electrolyte.

[0206] 2. Preparation of dry cells

[0207] The positive electrode active material is the ternary positive electrode material LiNi x Co y Mn 1-x-y O2 (0.9≤x<1,0<y≤0.1), conductive carbon black (Super-P Li), binder multi-walled carbon nanotubes (MWCNT), and binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 97.5%:1%:0.25%:1.25% to obtain a mixed material, and the mixed material is fully stirred in N-methylpyrrolidone (NMP) to obtain a positive electrode slurry for the corresponding positive electrode sheet.

[0208] The negative electrode active material artificial graphite, silicon oxide negative electrode, conductive agent conductive carbon black (Super-P Li), dispersant sodium carboxymethyl cellulose (CMC), binder polyacrylic acid (PAA), binder styrene butadiene rubber (SBR) are mixed in a mass ratio of 88.5%: 7.25%: 1%: 0.05%: 0.5%: 1.2%: 1.5% to obtain a mixed material, and the mixed material is fully stirred in deionized water to obtain the negative electrode slurry of the corresponding negative electrode sheet.

[0209] After stirring and slurrying, the positive electrode slurry and the negative electrode slurry are coated on 12μm thick aluminum foil and 6μm thick copper foil respectively. After drying, they are rolled, cut, slit, wound and other processes to make 20Ah soft-pack batteries.

[0210] 3. Preparation of batteries

[0211] S10, after thorough drying, inject the basic electrolyte (electrolyte prepared in step 1 above) into the dry cell, let it stand at room temperature for 24 hours, and then perform formation, exhaust and aging. The formation is performed at a current of 0.05C for 5 hours, followed by exhaust, vacuum degree -98kPa, exhaust time 5s, aging temperature 40℃, aging time 36 hours.

[0212] S20, the battery cell obtained in step S10 is subjected to secondary formation at a current of 0.2C, with a charge cut-off voltage of 4.2V; then, the battery cell is vented with a vacuum degree of -98kPa and a venting time of 5s; and then, a conventional lithium-ion battery is obtained after conventional capacity division.

[0213] Comparative Example 2

[0214] Comparative Example 2 is substantially the same as Example 1, except that:

[0215] In the preparation of the battery, in step S10, bromoacrylate is replaced with perfluoroalkylethyl methacrylate (CAS: 65530-66-7).

[0216] The rest are the same as in Example 1.

[0217] Comparative Example 3

[0218] Comparative Example 3 is substantially the same as Example 1, except that:

[0219] In the preparation of the battery, in step S10, the cross-linking agent is 1,4-butanediol diacrylate (CAS: 1070-70-8).

[0220] The rest are the same as in Example 1.

[0221] Performance Testing

[0222] The batteries prepared in the above-mentioned embodiments and comparative examples were subjected to cycle performance test, safety performance test and ion conductivity test.

[0223] (1) Cycle performance test: Use a Blue Electric charge and discharge tester to charge the battery at 0.5C constant current to 4.2V at room temperature (25°C), then charge it at 4.2V at constant voltage to a current of 0.05C, and then discharge it at 1C constant current to 2.5V. Record the discharge capacity of the first cycle, which is recorded as C0. Repeat the above steps for 1000 cycles and record the discharge capacity of the 1000th cycle, which is recorded as C1. Then, the cycle capacity retention rate after 1000 cycles = (C1 / C0) × 100%.

[0224] (2) Safety performance test: After the battery is fully charged, place the battery on a flat heating device with its surface in direct contact with the battery surface. Heat the sample continuously at a power of 300W until thermal runaway occurs or the temperature at the monitoring point reaches 300°C. Then turn off the heating device and observe for 1 hour to see if there is any smoke, fire or electrolyte leakage.

[0225] (3) Ionic conductivity test: Assemble a button-type battery cell of "stainless steel sheet / cellulose film / stainless steel sheet", add 100 μL of the precursor solution in each embodiment and comparative example, and finally place the battery cell in a 70°C oven for 24 hours to solidify the electrolyte gel. Then, measure the film thickness L, steel sheet area S and body impedance Rb, and calculate the ionic conductivity according to the formula σ=L / (Rb×S).

[0226] The test results are shown in Table 1 below.

[0227] Table 1 Battery performance test results of various embodiments and comparative examples

[0228]

[0229] It can be seen from the data in Table 1 that, compared with Comparative Examples 1-3, the solid-state batteries using the flame-retardant gel electrolytes prepared in Examples 1-7 of the present invention have improved cycle capacity retention, that is, improved battery cycle performance, and have good flame retardant properties and ionic conductivity, thereby improving battery safety and electrochemical performance.

[0230] By comparing comparative example 1 with embodiment 1, it can be seen that the battery of comparative example 1 uses a conventional liquid electrolyte, which has a high ionic conductivity but a high safety risk, and there are fire and electrolyte leakage. The flame-retardant gel electrolyte provided by the embodiment of the present invention not only has better flame retardancy, but also only smoke and no electrolyte leakage, thereby improving safety performance and improving battery cycle performance.

[0231] By comparing comparative example 2 with example 1, it can be seen that the electrolyte of the battery in comparative example 2 uses a perfluoroalkylethyl methacrylate monomer, whose CF bond energy is large, cannot effectively capture free radicals, and has a high thermal decomposition temperature, so the flame retardant performance is poor and still ignites. The example of the present invention uses a bromoacrylate monomer, in which the bond energy of the C-Br bond is weaker than that of the CF bond, and the flame retardant effect of the bromine-containing flame retardant polymer is better than that of the fluorine-containing flame retardant polymer agent, thereby improving the flame retardant performance, that is, improving the safety performance of the battery.

[0232] By comparing comparative example 3 with example 1, it can be seen that the electrolyte of the battery in comparative example 3 uses 1,4-butanediol diacrylate as a crosslinking agent. Although it has certain flame retardant properties and good safety performance, it reduces the battery's cycle performance and ionic conductivity, and reduces the battery's electrochemical performance. The embodiment of the present invention uses polyethylene glycol diacrylate crosslinking agent, which can provide good crosslinking reaction sites and form a crosslinked network polymer. At the same time, the -CH2CH2O- segment in its molecular structure can provide more electron-donating sites, which can be used to dissolve a large amount of lithium salts, and thus has higher ionic conductivity; and has higher chemical and thermal stability, which is conducive to improving the stability of the gel electrolyte, making the battery performance stable and long-lasting, thereby improving the battery's cycle performance.

[0233] Parts of the present invention that are not described in detail are well known to those skilled in the art.

[0234] The basic principle of the present invention is described above in conjunction with specific embodiments. However, it should be pointed out that the advantages, strengths, effects, etc. mentioned in the present invention are only examples and not limitations, and it cannot be considered that these advantages, strengths, effects, etc. must be possessed by each embodiment of the present invention. In addition, the specific details disclosed above are only for the purpose of illustration and facilitation of understanding, rather than limitation, and the above details do not limit the present invention to being implemented by adopting the above specific details.

[0235] It should be noted that the term "and / or" or " / " used in this document is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. The singular forms of "a", "the" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0236] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A, B are listed, the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, C are listed, the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.

[0237] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A flame retardant gel electrolyte, characterized in that: including flame retardant polymers and electrolytes; Wherein, the flame retardant polymer has the chemical formula shown in the following formula I: Formula I; Wherein, the R includes at least one of a brominated alkyl group or a brominated alkenyl group, and the brominated group is partially substituted or fully substituted; the values ​​of n, m1, m2, and m3 are in the range of 3 to 30 respectively; The flame retardant polymer is a cross-linked product of a polymer monomer and a cross-linking agent; the polymer monomer includes brominated acrylate, and the cross-linking agent includes polyethylene glycol diacrylate; The mass ratio of the crosslinking agent to the polymer monomer is (2-4):1; The mass ratio of the polymer monomer to the electrolyte is (1% to 3%):

1.

2. The flame-retardant gel electrolyte according to claim 1, characterized in that: The electrolyte comprises a lithium salt, an organic solvent and a functional additive; Wherein, the functional additive comprises at least one of vinylene carbonate, fluoroethylene carbonate, 1,3-propane sultone or vinylene sulfate; and / or, The mass percentage of the functional additive in the electrolyte is 0.5% to 5%.

3. The method for preparing a flame-retardant gel electrolyte according to any one of claims 1 to 2, characterized in that: The method comprises: Mixing a flame retardant polymer and an electrolyte to obtain a flame retardant gel electrolyte; Wherein, the raw materials for preparing the flame retardant polymer include polymer monomers and cross-linking agents; The polymer monomer includes bromoacrylate, and the cross-linking agent includes polyethylene glycol diacrylate.

4. The method for preparing a flame-retardant gel electrolyte according to claim 3, characterized in that: The bromoacrylate has the chemical formula shown in the following formula II: Formula II; Wherein, R comprises at least one of a brominated alkyl group or a brominated alkenyl group, and the brominated group is partially substituted or fully substituted; and / or, The average molecular weight of the polyethylene glycol diacrylate is 600-1500.

5. The method for preparing a flame-retardant gel electrolyte according to claim 3, characterized in that: The mass ratio of the crosslinking agent to the polymer monomer is (2-4):1; and / or, The mass ratio of the polymer monomer to the electrolyte is (1% to 3%):

1.

6. The method for preparing a flame-retardant gel electrolyte according to any one of claims 3 to 5, characterized in that: The raw materials for preparing the flame retardant polymer further include an initiator; and / or, The method comprises the following steps: Mixing polymer monomers, a cross-linking agent, an initiator and an electrolyte to obtain a precursor solution; The precursor solution is polymerized under heating and pressure conditions to form a cross-linked flame retardant polymer.

7. The method for preparing a flame-retardant gel electrolyte according to claim 6, characterized in that: The polymerization reaction conditions include: reaction temperature of 60°C to 90°C, reaction pressure of 0.2MPa to 1.5MPa, reaction time of 12h to 48h; and / or, The mass ratio of the initiator to the polymer monomer is (0.1-0.5):1; and / or, The initiator includes at least one of azobisisobutyronitrile, sodium persulfate or tert-butyl peroxide.

8. A battery, characterized in that: The battery comprises: A dry cell, the dry cell comprising a positive electrode and a negative electrode; and The flame retardant gel electrolyte according to any one of claims 1 to 2 or the flame retardant gel electrolyte prepared by the method according to any one of claims 3 to 7.

9. A method for preparing a battery, characterized in that: The method comprises: Mixing polymer monomers, a cross-linking agent, an initiator and an electrolyte to obtain a precursor solution; The precursor solution is injected into a dry battery cell, and after standing at room temperature, forming and aging, an in-situ hot pressing polymerization reaction is carried out to obtain a battery having the flame retardant gel electrolyte according to any one of claims 1 to 2.

10. The method for preparing a battery according to claim 9, characterized in that: The conditions of the in-situ hot pressing polymerization reaction include: reaction temperature of 60°C to 90°C, reaction pressure of 0.2MPa to 1.5MPa, reaction time of 12h to 48h; and / or, The temperature of the room temperature static state is 22°C to 28°C, and the time of the room temperature static state is 24h to 48h; The formation current is 0.01C to 0.1C, the formation temperature is 22°C to 28°C, and the formation time is 2h to 10h; and / or, The aging temperature is 35°C to 45°C, and the aging time is 12h to 48h; and / or, After the in-situ hot pressing polymerization reaction, the steps of secondary formation, exhaust and volume separation are also included; wherein the current of the secondary formation is 0.1C to 0.5C, and the charging cut-off voltage is 4.2V to 4.35V; and / or, The exhaust time is 5s to 30s, and the exhaust vacuum bag is -98kPa to -50kPa.